Macular Amyloidosis and Epstein-Barr Virus - Yalda Nahidi; Naser Tayyebi Meibodi; Zahra Meshkat; Narges Nazeri (Dermatology Research and Practice)
Background. Amyloidosis is extracellular precipitation of eosinophilic hyaline material of self-origin with special staining features and fibrillar ultrastructure. Macular amyloidosis is limited to the skin, and several factors have been proposed for its pathogenesis. Detection of Epstein-Barr virus (EBV) DNA in this lesion suggests that this virus can play a role in pathogenesis of this disease. Objective. EBV DNA detection was done on 30 skin samples with a diagnosis of macular amyloidosis and 31 healthy skin samples in the margin of removed melanocytic nevi by using PCR. Results. In patients positive for beta-globin gene in PCR, BLLF1 gene of EBV virus was positive in 23 patients (8 patients in case and 15 patients in the control group). There was no significant difference in presence of EBV DNA between macular amyloidosis (3.8%) and control (23.8%) groups (P=0.08). Conclusion. The findings of this study showed that EBV is not involved in pathogenesis of macular amyloidosis.